The genetic control of HLA-A and B antigens in somatic cell hybrids: requirement for beta2 microglobulin. - Arce-Gomez, B; Jones, E; Barnstable, C; Solomon, E; Bodmer, W (1978)
The lymphoblastoid cell line Daudi lacks both HLA-A and B antigens and beta2 microglobulin. Somatic cell hybrids derived from a fusion between this line and D98/AH--2 were shown to express four HLA antigens not detectable on either parent cell, A1, A10(Aw26), Bw16(Bw38, Bw17. The initial definition by direct cytotoxicity assay was confirmed by absorption of reactions against target T lymphocytes, thus avoiding problems due to contaminating Ia antibodies, and by blocking the reactions by pretreatment with a chicken anti-human beta2 microglobulin serum. That the new specificities were due to the Daudi HLA region was confirmed by the finding that interspecific hybrids between Daudi and A9L, containing a single human chromosome 6, expressed A10 and Bw17. This also defined the haplotypes of Daudi as A10(Aw26), Bw17 and A1, Bw16(Bw38). The re-expression of the Daudi HLA-A and B antigens in two independent sets of hybrids indicates that it does not carry a mutation in the HLA region. It has previously been reported that somatic cell hybrids with Daudi, which contain chromosome 15, do not express human beta2 microglobulin. These results suggest that the reason for the lack of HLA-A and B antigens on Daudi is a secondary effect due to the mutation(s) in the beta2 microglobulin gene.